In Vivo Nuclear Molecular Imaging in Drug Development and Pharmacological Research - Yue, Xuyi (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue published one editorial, eight articles and four reviews from approximately one hundred authors. It aimed to provide cutting-edge research on pre-clinical development and the clinical translation of radiopharmaceuticals within the molecular imaging community. The Special Issue covered radioligand development, existing radiotracer optimization, imaging agent evaluation in animal models, the clinical production of radiopharmaceuticals, and investigative research on the use of molecular imaging probes in human subjects. We appreciate all the authors' significant contributions to this Special Issue and hope the readers will enjoy the content.